Caribbean Report 18-01-1990 - Crosskill, Hugh (anchor); Gopaul, Nanda Kishore (interviewee); Khan, Sharief (correspondent); Pastor, Robert (interviewee); Langridge, Dereck (interviewee); Redhead, Brian (correspondent); Gatting, Mike (interviewee); Lloyd, Clive (interviewee); Partridge, Frank (correspondent) (The British Broadcasting Corporation, 1990)
The program reports on the newly formed Guyanese Action for Reform and Democracy (GUARD) organization which is viewed as a forerunner to a new political party with the aim to foster social and political change in Guyana. Secondly, Caribbean politicians are concerned over the recent shift in the US fund in assisting the anti-drug programme from the Caribbean to Poland. Following the Financial News, the British owned Cable and Wireless Co. responds to criticisms from Vere Bird Jr., Communications Minister in Antigua and Barbuda who purports that the company has a strangle-hold on the telecommunications of the twin island. The final segment addresses the upcoming controversial tour of the English cricket team to South Africa and over Mike Gatting’s (England captain) remarks, “I know little about apartheid” at a news conference a year ago.
1. Headlines (00:00-00:44)
2. The newly formed Guyanese Action for Reform and Democracy movement is viewed as a forerunner to a new political party. Interview with Nanda Kishore, GUARD's coordinator, and Sharief Khan reports from Georgetown (00:44-03:37)
3. Shift in US foreign aid from the Caribbean to Poland. Telephone interview with Professor Bob Pastor, Emory University, Atlanta (03:38-07:00)
4. Financial News (07:01-07:37)
Keywords: Political parties -- Guyana.; Social movements -- Guyana.; Economic assistance -- United States.; Cable and Wireless (Firm).; Telecommunication -- Antigua and Barbuda.; Cricket -- Tournaments -- England.; Cricket -- Tournaments -- South Africa.; Sports and state -- South Africa.; Guyanese Action for Reform and Democracy (GUARD).